From ancient times to the present - Lamazhaa, Chimiza K. (The New Research of Tuva, 2010)
Book review of Kisel V.A. Trip for the red salt. Obsequies of Tuva from 18th to early 21st century. Saint-Petersburg: Science publishing house, 2009. 142 P.
Keywords: Saint Petersburg; Ethnography; V. p. Dyakonov; funeral rites; Tuva; the Russians in Tuva; archaeology